2010
DOI: 10.2528/pier10081008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Perpendicular Crossing Dielectric Waveguides With Various Typical Index Contrasts and Intersection Profiles

Abstract: Abstract-We present a rigorous 2D numerical study of the transmission, reflection and crosstalk coefficients of the perpendicular, identical dielectric crossing waveguide with various core-cladding index contrasts for both TE and TM polarizations. Our method is based on a hybrid frequency-domain finite-difference (FD-FD) technique computed with the cross-symmetry model. By varying the intersection profile, such as the circular, filleted, tapered and elliptical shapes, we achieve, even for a large 3.5 to 1.5 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…In Ref. [1] we conducted detail numerical calculations of B with the exact dispersion relation (Equations (27)-(28)) and found that ε LFE- 9 1 for all θ ∈ [0, 2π] and all V ∈ [0, π]. But for LFE-5, the relative B-K differences are much larger, thus ε LFE- 5 1 is not always satisfied.…”
Section: Numerical Verification Of the First-order Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [1] we conducted detail numerical calculations of B with the exact dispersion relation (Equations (27)-(28)) and found that ε LFE- 9 1 for all θ ∈ [0, 2π] and all V ∈ [0, π]. But for LFE-5, the relative B-K differences are much larger, thus ε LFE- 5 1 is not always satisfied.…”
Section: Numerical Verification Of the First-order Error Analysismentioning
confidence: 99%
“…From these FourierBessel coefficients we derived FD-like, compact nine-point stencils for the 2D Helmholtz equation. We show that CLF is capable of advancing existing FD-FD methods [5][6][7][8][9] by reducing the sampling density to just a little more than two points per wavelength, which is theoretical limit for spatial sampling.…”
Section: Introductionmentioning
confidence: 98%
“…Dielectric-loaded horns utilize the dominant or hybrid modes in the uniform dielectric waveguides to constitute the aperture-field distribution attenuating radially with low cross-polarization [2,[7][8][9]. A dielectric-loaded diagonal horn can concentrate most of the electromagnetic energy in the dielectric remaining minor fraction near the metal wall, producing a Gaussian field distribution in the dielectric cross-section [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We shall prove in future paper that high-order compact stencils like Eqs. (7), (9), and (10) can be derived from LFE-9 formulation.…”
Section: The Full 2d Lfe-9 Formulationmentioning
confidence: 99%
“…In recent years hybrid FD-FD methods have been successfully applied to study many time-harmonic electromagnetic problems and even complex dielectric waveguide devices [1][2][3][4][5][6][7][8][9]. When combined with effective transparent boundary conditions such as the PML [10,11] and the recently developed LM-TBC method [12], the hybrid FD-FD method can be quite computationally efficient for certain passive optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%